Antara Larangan dan Pengecualian: Ihwal Partisipasi Aktif Imam dalam Partai Politik dan dalam Jabatan Publik - Rikardus Jehaut (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article - inspired by the notorious case of an Indonesian priest in North Sumatra running for public office despite stern and repeated warnings from his bishop not to do so - aims to elaborate the theme of active participation of priests in politics in the light of can. 285 § 3 and can. 287, § 2 of Code of Canon Law, using the method of juridical exegesis and historical-critical analysis of various legal grounds and various affirmations of the Church's Magisterium. Through careful study, the author shows that the Church, while acknowledge the political right of priests as well as the provision for exeption, imposing a prohibition on them from participating actively in the political arena. The ratio legis behind such prohibition are threefold, namely safeguard canonically the identity and the mission of the priests; priest as a symbol of unity, fraternity and peace; respect for the peculiar duties of the laity in politics. The author argues that the priests should not be given a permission to take any public office and should not take sides in the area of party politics since there are no situation that make it necessary to intervene in that way. Key words: Active participation, politic, priest, prohibition, exeption